2006
DOI: 10.1140/epje/i2006-10012-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the stress response of two-dimensional dense granular packings

Abstract: We investigate the Green function of two-dimensional dense random packings of grains in order to discriminate between the different theories of stress transmission in granular materials. Our computer simulations allow for a detailed quantitative investigation of the dynamics which is difficult to obtain experimentally. We show that both hyperbolic and parabolic models of stress transmission fail to predict the correct stress distribution in the studied region of the parameters space. We demonstrate that the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We numerically study the linear, quasistatic response of systems near the jamming transition. The response of granular media has been widely-studied [11,12,13,14,15,16], but not, we believe, systematically as a function of the distance to the jamming point J. Nor does it seem to have been fully appreciated that the scaling behavior can essentially be captured within linear response.…”
mentioning
confidence: 88%
“…We numerically study the linear, quasistatic response of systems near the jamming transition. The response of granular media has been widely-studied [11,12,13,14,15,16], but not, we believe, systematically as a function of the distance to the jamming point J. Nor does it seem to have been fully appreciated that the scaling behavior can essentially be captured within linear response.…”
mentioning
confidence: 88%
“…For small enough forces this probes the Green's function of the granular packing and provides crucial information on the effective continuum description of the system. Experiments [77][78][79] and simulations [31,80,81] have shown that the spreading of the load inside the material is not universal but can be along a single broad peak, as is the case for isotropic linear elastic materials, or more anisotropically along two peaks. The response is found to depend on parameters such as friction coefficient, degree of disorder, coordination number and amplitude of applied force.…”
Section: B Response To a Point Forcementioning
confidence: 99%
“…Experimental and numerical works have shown that the linear stress response of granular systems to a point force is well described by (possibly anisotropic) elasticity [36,3,17,24,18,2,15]. In this section, we introduce the framework of orthotropic elasticity, with which numerical response profiles such as those displayed in Fig.…”
Section: Orthotropic Elastic Analysismentioning
confidence: 99%